Pengaruh Likuiditas dan Ukuran Perusahaan Terhadap Kinerja Keuangan dari Perusahaan Teknologi di Bursa Efek Indonesia - Anggun Veby Safitriana (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted to identify the influence of liquidity and company size on the company's financial performance. This objective aims to determine whether the Company's liquidity level, such as the current ratio, quick ratio and total assets, has a significant relationship with the Company's financial performance. The results of this research show that liquidity has a positive effect on the financial performance of technology companies listed on the BEI in 2020 - 2022. The higher the level of company liquidity, the higher the company's financial performance, that company size influences the financial performance of technology companies listed on the BEI in 2020 - 2022. 2020 - 2022. The size of the company does not affect the size of the company's financial performance